Intergenerational learning in Taiwanese preschools: Theoretical foundations and core principles for educational renewal - Shih, Yi-Huang; Liu, Yi-Yi; Chiu, Kun-I; Chiang, Yu-Ming; Chiang, Wen-Wei (Edelweiss Applied Science and Technology, 2025)
Intergenerational Learning (IGL) is an educational approach that facilitates structured interactions between individuals from different generations, fostering the reciprocal exchange of knowledge, values, and skills. This pedagogical framework not only strengthens intergenerational relationships but also contributes to the holistic well-being of both older adults and young children. Moreover, IGL programs function as a meaningful form of social participation, promoting active aging among older adults while enriching the developmental experiences of younger learners. The implementation of IGL initiatives is widely acknowledged as an effective strategy for cultivating collaborative and transformative learning experiences. Furthermore, the theoretical framework of this study draws upon the social constructivist perspective, Bandura’s social learning theory, Piaget’s cognitive development theory, and Mezirow’s transformative learning theory. These perspectives collectively inform an understanding of how individuals construct meaning through social interaction, observation, cognitive development, and critical reflection. The core principles underpinning the study include reciprocity, social cohesion, cultural transmission, and sustainability. These interconnected concepts serve as foundational pillars for fostering inclusive, collaborative, and culturally responsive educational practices aimed at long-term societal well-being. In light of these considerations, this article aims to foster the theoretical foundations and core principles of intergenerational learning in Taiwanese preschools, with a focus on fostering educational renewal.